Robust Projected Weakening of Winter Monsoon Winds Over the Arabian Sea Under Climate Change. Issue 19 (4th October 2017) - Parvathi, V.; Suresh, I.; Lengaigne, M.; Izumo, T.; Vialard, J.
Abstract: The response of the Indian winter monsoon to climate change has received considerably less attention than that of the summer monsoon. We show here that all Coupled Model Intercomparison Project Phase 5 (CMIP5) models display a consistent reduction (of 6.5% for Representative Concentration Pathways 8.5 and 3.5% for 4.5, on an average) of the winter monsoon winds over the Arabian Sea at the end of 21st century. This projected reduction weakens but remains robust when corrected for overestimated winter Arabian Sea winds in CMIP5. This weakening is driven by a reduction in the interhemispheric sea level pressure gradient resulting from enhanced warming of the dry Arabian Peninsula relative to the southern Indian Ocean. The wind weakening reduces winter oceanic heat losses to the atmosphere and deepening of convective mixed layer in the northern Arabian Sea and hence can potentially inhibit the seasonal chlorophyll bloom that contributes substantially to the Arabian Sea annual productivity. Plain Language Summary: The Indian summer monsoon response to climate change has been previously the focus of many studies. The Indian winter monsoon‐projected response to climate change is, however, largely unexplored. This is the first study to report a robust weakening of the Indian winter monsoon winds over the Arabian Sea in two Coupled Model Intercomparison Project Phase 5 scenarios (an unmitigated and a mitigated one). The wind weakening leads to reduced winter oceanic convective overturning in the northern Arabian Sea. This winter convection is the key mechanism for a productivity (winter) bloom that strongly contributes to the Arabian Sea annual productivity. The projected winter monsoon weakening may thus reduce the Arabian Sea productivity. We also show a rainfall increase that could affect water supply in tropical Indian Ocean islands and Eastern Africa. Key Points: This study reports a robust reduction of the northeast monsoon winds over the Arabian Sea under two climate change scenarios The wind weakening is driven by a reduction of the Interhemispheric sea level pressure gradient Weakening of winds leads to a reduced winter mixed layer deepening in the northern Arabian Sea and hence less oceanic productivity